COSTS, MARGINS AND PRICE SPREAD ACROSS THE MARKETING CHANNELS OF DRY FISH IN JAGIROAD DRY FISH MARKET OF MORIGAON DISTRICT, ASSAM - KASHYAP, DIPANJAN; BHATTACHARJYA, B. K. (Journal of the Inland Fisheries Society of India, 2021)
Five marketing channels of dry fish were identified in Jagiroad market of Morigaon district, Assam, India, of which Channel I (dry fish producer – assembler - commission agent - wholesaler - retailer - consumer), Channel II (DFP - CA - WS - R - C) and Channel IV (DFP - WS - R - C) were the most dominant ones contributing to 90.55% of total volume of dry fish sold in the market. Marketing costs per kg was estimated as Rs. 45.23, 39.15 and 36.29 in channels I, II and IV, respectively. Differences in margins earned by various market intermediaries were Rs. 71.25, 66.38 and 57.95 in channels I, II and IV respectively. The share of producers in consumer’s rupee was 36.27%, 41.17% and 45.99% in Channels I, II and IV respectively. The study showed that the share of dry fish producers in consumer’s rupee is inversely proportional to the number of intermediaries involved in the marketing channel. Key words: Dry fish, marketing channel, marketing costs/ margin, price spread